2014
DOI: 10.1371/journal.pone.0098877
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cell-Mediated Immune Responses in Mice by DNA Vaccines That Express Hepatitis C Virus NS3 Mutants Lacking Serine Protease and NTPase/RNA Helicase Activities

Abstract: Effective therapeutic vaccines against virus infection must induce sufficient levels of cell-mediated immune responses against the target viral epitopes and also must avoid concomitant risk factors, such as potential carcinogenic properties. The nonstructural protein 3 (NS3) of hepatitis C virus (HCV) carries a variety of CD4+ and CD8+ T cell epitopes, and induces strong HCV-specific T cell responses, which are correlated with viral clearance and resolution of acute HCV infection. On the other hand, NS3 posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…They subsequently demonstrated comparable immune response following immunization using non-catalytic NS3 mutants compared to wild type NS3. Their results indicated that the comparable effectiveness and reduced bioactivity of these immunogens, would prove to be efficient alternatives to wild type HCV proteins in DNA vaccines against HCV [ 28 ]. Gene electrotransfer of a DNA vaccine encoding an optimized version of the nonstructural region of HCV (from NS3 to NS5B) also induced substantially more potent, broad, and long-lasting CD4+ and CD8+ cellular immunity than naked DNA injection in mice and in rhesus macaques, as measured by a combination of assays, including IFN-γ ELISPOT, intracellular cytokine staining, and CTL assays [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…They subsequently demonstrated comparable immune response following immunization using non-catalytic NS3 mutants compared to wild type NS3. Their results indicated that the comparable effectiveness and reduced bioactivity of these immunogens, would prove to be efficient alternatives to wild type HCV proteins in DNA vaccines against HCV [ 28 ]. Gene electrotransfer of a DNA vaccine encoding an optimized version of the nonstructural region of HCV (from NS3 to NS5B) also induced substantially more potent, broad, and long-lasting CD4+ and CD8+ cellular immunity than naked DNA injection in mice and in rhesus macaques, as measured by a combination of assays, including IFN-γ ELISPOT, intracellular cytokine staining, and CTL assays [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous clearance of HCV in a small portion of the infected hosts has spurred the search for prophylactic and therapeutic vaccines against this viral infection. NS3 protein is one of the more genetically conserved antigens in the highly variable HCV genome and the importance of its specific T cell responses in clearance of acute infection has been shown [25].The protease and helicase activities of the protein have been mapped to the N-terminal one third and C-terminal two thirds of the full-length polypeptide respectively [26].The enzymatic activities of NS3 while pivotal in viral lifecycle may interfere with host defense mechanism, therefore in this study a truncated form of the protein lacking protease and helicase activity was used [7]. Truncated fragment however, contained a number of T cell epitopes that ranked very high in in silico analysis ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…NS3 is a 69 kDa multi-functional hydrophobic protein with serine protease and nucleoside triphosphatase (NTPase)/RNA helicase activities involved in processing of the viral polyprotein and viral RNA replication. It has been shown that NS3 induces immune responses capable of clearing HCV, making it an attractive candidate for a therapeutic vaccine [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Initial results suggested the safety and immunogenicity of the vaccine, and it is now in phase II clinical trials for HCV infection (NCT01335711). Ratnoglik et al constructed a series of DNA vaccines that express NS3 with mutations in the catalytic triad of the serine protease and the NTPase/RNA helicase domain [ 137 ], which overcame the effects of NS3 on normal cell function [ 138 ].…”
Section: Therapeutic Vaccines Against Infectious Diseasesmentioning
confidence: 99%